University Environment and Its Relationship to The Life Skills Among Female Students at The Faculty of Education in Taibah University - Helabi, Manal Mubarak (Journal of Educational and Psychological Sciences, 2020)
This study aimed at identifying the physical and human Constituents for university environment as seen by female students, determining the relationship between the university environment and life skills, and identifying the differences between university environment and life skills according to the following variables: academic specialization and academic level. The sample of the study consisted of 181 female students, 146 were from special education department and 35 female students from art education department, the researcher applied the descriptive analytical approach. To achieve the goal of the study the researcher prepared a questionnaire for university environment consisted of 19 fields and a questionnaire for life skills included 5 skills Prepared Alrabani (2008). The following statistical treatments were applied: arithmetic means, standard deviation, T- test, one- way Anova, Scheffe test, the findings of the study indicated the following results: there is a highly significant correlation between mean of the grades of university environment questionnaire and life skills questionnaire, there is no significant differences attributed to the academic specialization between the mean of the grades of the university environment questionnaire except one field "the central library", there are significant differences attributed to the academic level on some fields of the university environment questionnaire, there are no significant differences between the grades of the life skills questionnaire. In light of these findings the researcher proposed some recommendations and suggestions.